Tuberculosis as a differential for bilateral adrenal masses in the UK. Issue 5 (28th May 2019) - Arambewela, Maulee; Ross, Richard; Pirzada, Omar; Balasubramanian, Sabapathy P
Abstract : Primary adrenal insufficiency (PAI) is a potentially fatal disease. Adrenal tuberculosis(TB) causing PAI is rare in the developed world. We present a seemingly well, 78-year-old Caucasianwoman in the UK who developed adrenal crisis following elective hip surgery. Biochemical tests confirmed PAI and steroid replacement was initiated. Imaging of the abdomen demonstrated bilateral adrenal masses and a fluorodeoxyglucose positron emission tomography (FDG-PET) scan showed increased uptake in both adrenals suggestive of malignancy. Following a retroperitoneoscopic left adrenalectomy, histology showed caseating necrosis with xanthogranulomatous inflammation favouring a diagnosis of TB. She was commenced on anti-TB treatment. Diagnosing adrenal TB in the west can be challenging especially in the absence of extra-adrenal TB. FDG-PET scans can be falsely positive in presence of chronic active inflammatory conditions, such as TB, and a tissue diagnosis is required. It is important that clinicians remain vigilant of this important disease, which can masquerade as malignancy.